High‐Density Nanopore Confined Vortical Dipoles and Magnetic Domains on Hierarchical Macro/Meso/Micro/Nano Porous Ultra‐Light Graphited Carbon for Adsorbing Electromagnetic Wave - Huang, Wenhuan; Zhang, Xingxing; Chen, Jiamin; Qiu, Qiang; Kang, Yifan; Pei, Ke; Zuo, Shouwei; Zhang, Jincang; Che, Renchao (Advanced science, 2023)
Atomic‐level structural editing is a promising way for facile synthesis and accurately constructing dielectric/magnetic synergistic attenuated hetero‐units in electromagnetic wave absorbers (EWAs), but it is hard to realize. Herein, utilizing the rapid explosive volume expansion of the CoFe‐bimetallic energetic metallic triazole framework (CoFe@E‐MTF) during the heat treatment, the effective absorption bandwidth and the maximum absorption intensity of a series of atomic CoFe‐inserted hierarchical porous carbon (CoFe@HPC) EWAs can be modified under the diverse synthetic temperature. Under the filler loading of 15 wt%, the fully covered X and Ku bands at 3 and 2.5 mm for CoFe@HPC800 and the superb minimum reflection loss ( RL min ) of −53.15 dB and specific reflection loss ( SRL ) of −101.24 dB mg −1 mm −1 for CoFe@HPC1000 are achieved. More importantly, the single‐atomic chemical bonding among Co─Fe on the nanopores is captured by extended X‐ray absorption fine structure, which reveals the formation mechanism of nanopore‐confined vortical dipoles and magnetic domains. This work heralds the infinite possibilities of atomic editing EWA in the future.